(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Rapid urbanization and the escalating demand for affordable urban housing have intensified the search for sustainable, cost-effective building materials. Interlocking Stabilized Soil Block (ISSB) technology offers a promising, low-carbon alternative to conventional fired bricks and concrete blocks by utilizing locally sourced soil compressed with a minimal stabilizing agent (such as cement or lime). However, despite its proven economic and environmental advantages, widespread adoption in urban housing developments remains limited. This paper investigates the critical challenges and emerging opportunities surrounding the large-scale integration of ISSB technology in urban contexts. Through a mixed-methods approach—combining a comprehensive literature review, comparative cost-benefit analyses, and stakeholder interviews within the construction sector—the study identifies major barriers to adoption. These include rigid or outdated building regulatory frameworks, deeply entrenched negative public perceptions associating soil-based materials with low-income or temporary housing, and supply chain inconsistencies regarding block quality and production scale. Conversely, the research highlights significant opportunities, particularly driven by shifting green building policies, rising carbon tax pressures, and the urgent need for climate-resilient urban infrastructure. The paper concludes with a strategic framework aimed at policymakers, developers, and engineers to standardize ISSB production, update municipal building codes, and incentivize sustainable development, positioning ISSB technology as a viable cornerstone for future eco-friendly urban housing.